The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1097/brs.0000000000001721
|View full text |Cite
|
Sign up to set email alerts
|

Is Obesity in Adolescent Idiopathic Scoliosis Associated With Larger Curves and Worse Surgical Outcomes?

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 10 publications
4
25
0
Order By: Relevance
“…It is interesting to note that the OB patients were the youngest on average (13.7 vs 14.5 years for NW patients vs 14.1 years for OW patients, p < 0.001). This has been shown previously 11 and may be attributable to the fact that obese patients can present with worse curves initially, or to the decreased effectiveness of brace treatment. 14 Likewise, the OB patients were more likely to undergo fusion of 13 or more spinal levels, suggesting that they, in fact, may present with more severe curves, as has been postulated previously.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…It is interesting to note that the OB patients were the youngest on average (13.7 vs 14.5 years for NW patients vs 14.1 years for OW patients, p < 0.001). This has been shown previously 11 and may be attributable to the fact that obese patients can present with worse curves initially, or to the decreased effectiveness of brace treatment. 14 Likewise, the OB patients were more likely to undergo fusion of 13 or more spinal levels, suggesting that they, in fact, may present with more severe curves, as has been postulated previously.…”
Section: Discussionmentioning
confidence: 52%
“…10 Interestingly, other studies have not found higher complication rates in obese patients undergoing AIS surgery. 9,11,18 Although Hardesty et al showed a difference in operative times and blood loss, their complication rate was not significantly different between normal-weight (15%) and obese (14%) patients (p = 0.950). Li et al retrospectively analyzed the outcomes of 588 patients (454 normal weight, 63 overweight, and 71 obese patients), finding no significant differences in intraoperative or postoperative complications between the normal-weight and overweight patients (postoperative: 21.8% vs 23.9%, p = 0.612) or between the normal-weight and obese patients (postoperative: 21.8% vs 28.2%, p = 0.234).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…It is understandable that external body dimension does not necessarily match with the internal anatomical configuration910. Conversely, some studies suggest a higher BMI at presentation to a scoliosis clinic is associated with larger Cobb angles111213.…”
mentioning
confidence: 99%